Pendampingan Kegiatan “Tok..Tok..Tok..: Training of Kader” sebagai Upaya Peningkatan Keterampilan Kader dalam Pelaksanaan Skrinning Hipertensi dan Diabetes di Desa Ngrandu, Kabupaten Ponorogo, Jawa Timur: Penelitian - Ineztia Sila Widya Prasanti; Nurul Fitriyah; Yustinus Denny Ardyanto; Rayinda Prasetya Putri; Aqila Rachmasari; Naufal Aulia Bagas Putra; Alifia Nezaluna Amalia Iasyah; Safira Aurellia Salsabila; Raissyah Fatika Rahma Dewi; Fathiyya Defrina Putri; Tuty Alawiyah; Gita Mahendra Putranto; Cindy Aulia Suryaningrum; Sevina Nabilah Khansa (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Non-communicable diseases (NCDs) such as hypertension and diabetes mellitus pose significant health challenges globally and in Indonesia. This study aims to evaluate the effectiveness of the “Tok..Tok..Tok..: Training of Cadres” program in improving the skills of health cadres in conducting hypertension and diabetes screening in Ngrandu Village, Ponorogo Regency. A descriptive observational design was employed involving 50 cadres participating in the training. Data were collected using Knowledge, Attitude, and Practice (KAP) questionnaires, practice observation sheets, and in-depth interviews. Descriptive statistical analysis and data triangulation were applied. Results showed that 84% of cadres attended the training, with over 50% achieving scores ≥70 in all assessed skill aspects. The training significantly enhanced cadres’ competencies in screening, educative communication, and referral determination. The study concludes that the “Tok..Tok..Tok..” training effectively strengthens cadre capacity, supporting the success of Primary Service Integration (ILP) at the village level. Future research should explore long-term impacts and digital training modules.